Development and Application of in vivo 2H Magnetic Resonance - Cocking, Daniel (2024)
Use of deuterium (2H) as a tracer combined with Magnetic Resonance (MR) Imaging/Spectroscopy could potentially replace diagnostic techniques that use ionising radiation such as Positron Emission Tomography (PET) imaging. Proton (1H) MR scanning is used clinically and in research, but 2H comes with a decreased Signal-to-Noise Ratio (SNR). However, thanks to the reduced T1 relaxation times of 2H, much of the SNR loss can be compensated by rapid averaging to allow for reasonable scan times. In this thesis deuterium magnetic resonance has been implemented in healthy human participants in vivo on both 3T and 7T MR scanners to investigate metabolism and key inherent MR parameters of 2H. 7T Multi-Echo Gradient-Echo (MEGE) images at a range of Repetition Times (TR) values were used to obtain relaxation times (T1 and T2∗) in CerebroSpinal Fluid (CSF), Grey Matter (GM) and White Matter (WM) in subjects who had ingested heavy water (D2O) to increase the 2H concentration by ∼x100 times. The 2H signal time-course was also measured following initial loading and compared to estimated changes in 2H concentration based on consideration of body water mixing. Glucose with two or seven attached 2H atoms (glucose-d2/d7 respectively) was ingested by healthy human participants. The change in in vivo downstream 2H metabolite maps of semi-heavy water (HDO), glucose, Glx (combination of glutamate and glutamine) and lactate was tracked in different brain regions using Magnetic Resonance Spectroscopic Imaging (MRSI) at 7T. An increased SNR was noted for all metabolites following glucose-d7 ingestion. Time-courses for each metabolite were obtained and d7/d2 signal ratios were explained by the differing numbers of labels. Lipid metabolism and the quadrupolar splitting of 2H signals in vivo was investigated using a clinical 3T scanner in subjects who had ingested D2O. An increase in 2H lipid signal was detected. Quadrupolar splitting was quantified in skeletal muscle at different angles with respect to the B0 field, along with the isolation of a Double Quantum Filtered (DQF) signal.